Financial Viability of Tier-II Cooperative Credit Institutions–A Study of District Central Cooperative Banks in India - Chander, Ramesh; Chandel, Jai Kishan (Indian Journal of Finance, 2011)
The cooperative credit institutions, being important constituents of the Indian financial system, are judged by the role assigned to them, the expectations they are supposed to fulfil, their number and the number of offices these operate. Cooperative banks in India have been working at three levels, viz. At State (Tier I), District (Tier II) and Village level (Tier III). Many cooperative banks became insolvent and others are on the verge of mergers or acquisitions. The scams in cooperative sector, failure and closure of unviable branches, imposition of penalty by RBI or NABARD and payment of heavy money claims by DICGC due to bankruptcy of cooperative banks are few significant reasons to force for having a look into the financial affairs of these institutions. In the present study, an attempt is made to analyze the financial and operational performance of 372 DCCBs for the period of ten years (1998-2008) by implementing CAMEL model, Altman Z-score model and other financial parameters. The results reveal that the recovery percentage has been high in these banks, but the banks did poorly on other financial parameters like-capital adequacy, liquidity, earning quality and management efficiency. These banks had been a part of bankruptcy (weak performance) zone throughout the study period. The Banks should emphasize on generating more profits by efficient utilization of their capital, assets and improving the productive efficiency of their employees.